Integrating spatial vitality and node-place model to evaluate and classify metro station areas in Wuhan - Tao Wu; Mingjing Li; Linna Gao; Ye Zhou (Frontiers of Architectural Research)
Numerous metropolises worldwide have adopted transit-oriented development (TOD) as a sustainable urban development tactic. And the node-place model is the most commonly used model for TOD typology. However, the spatial vitality, one of the most fundamental aspects of TOD, has not been systematically taken into account in the node-place model. Therefore, this article introduces vitality as a third dimension into node-place model and develops the node-place-vitality (NPV) model, aiming to comprehensively re-classify and re-evaluate TOD performance. The independent weight coefficient method is used to compute place values, node values, vitality values, and overall TOD degree. Moreover, the categorization of TOD typologies makes use of the K-means++ clustering approach. The model is employed in a case study in Wuhan, China. The results show that the TOD degree exhibits a spatial discrepancy, characterized as “high-medium-low” from the center to the periphery, not only in the whole city but also in the three towns. The geographical characteristics of TOD degree within station catchment area are revealed by the heat map. Five TOD types are identified and they present obvious spatial differentiation. The approach proposed in this paper furnishes urban planners and decision-makers with a scientific instrument for assisting TOD planning and strategies designing.